Voltammetric determination of leucovorin in pharmaceutical samples - Martinková, Pavlína; Kränková, Barbora; Šelešovská, Renáta; Janíková, Lenka (Univerzita Karlova. Přírodovědecká fakulta, 2017)
Voltammetric behavior of leucovorin has been investigated for the first time using boron-doped diamond electrode (BDDE) and the method for its determination was developed. Leucovorin provides two well-developed oxidation peaks at about +900 and +1450 mV (pH 5) on BDDE. Britton-Robinson buffer (pH 3.0) was chosen as an optimal supporting electrolyte for its determination using differential pulse voltammetry (DPV) with optimized parameters. Limit of detection 1.5×10−8 mol L−1 was reached for leucovorin determination and linear dynamic range 1.5×10−7-2.5×10−5 M was obtained. Relative standard deviation of repeated measurements (RSDM(11) = 0.7 %) and relative standard deviations of repeated determinations (RSDD(5) < 3.0 %) were calculated to confirm very good results. Applicability of the proposed method was verified by an analysis of a pharmaceutical preparation.
Voltametrické stanovení leukovorinu ve farmaceutických přípravcích
Keywords: Leucovorin; Oxidation; Boron-doped diamond electrode; Differential pulse voltammetry; Leukovorin; Oxidace; borem dopovaná diamantová elektroda; diferenční pulzní voltametrie